2020
DOI: 10.12962/j20882033.v31i1.5511
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Zeolitic Imidazolate Framework-8 (ZIF-8)/Al2O3 Composite

Abstract: Metal-organic framework (MOF) such as ZIF-8 is the tremendous porous material applied in many fields due to high specific surface area and excellent regularity of pores. One technique to improve the physical properties of ZIF-8 with the formation of a composite between a metal oxide and MOF. ZIF-8 and ZIF-8/ 2 3 were successfully synthesized by the solvothermal method with an variation of 19%, 38%, and 76%. The ZIF-8/ 2 3 were characterized by XRD, FTIR, SEM, and 2 Physisorption. The diffractogram shows that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
(13 reference statements)
1
4
0
Order By: Relevance
“…The same peaks can be found in all samples at 7.40, 10.43, 12.7, and 18.0°, which correspond to the diffraction planes (011), (002), (112), and (222), respectively, which are consistent with the XRD patterns of MOFs . The data demonstrates that ZIF-8 exhibits great crystallinity and that all samples are in pure phases and are isostructural, indicating that there are sufficient binding proteins to produce co-crystallization, that is, uniform tiny molecules of biofluids . The DLS analysis revealed the particle size distribution of the Zn–Co, Zn–Cu, and Zn–Ni MOFs, with an average size of 442.5 ± 10.96 nm for Zn–Co, 1362 ± 37.72 nm for Zn–Cu, and 1069 ± 29.87 nm for Zn–Ni (Figure a and Table S-1).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The same peaks can be found in all samples at 7.40, 10.43, 12.7, and 18.0°, which correspond to the diffraction planes (011), (002), (112), and (222), respectively, which are consistent with the XRD patterns of MOFs . The data demonstrates that ZIF-8 exhibits great crystallinity and that all samples are in pure phases and are isostructural, indicating that there are sufficient binding proteins to produce co-crystallization, that is, uniform tiny molecules of biofluids . The DLS analysis revealed the particle size distribution of the Zn–Co, Zn–Cu, and Zn–Ni MOFs, with an average size of 442.5 ± 10.96 nm for Zn–Co, 1362 ± 37.72 nm for Zn–Cu, and 1069 ± 29.87 nm for Zn–Ni (Figure a and Table S-1).…”
Section: Resultssupporting
confidence: 71%
“…39 The data demonstrates that ZIF-8 exhibits great crystallinity and that all samples are in pure phases and are isostructural, indicating that there are sufficient binding proteins to produce cocrystallization, that is, uniform tiny molecules of biofluids. 40 The DLS analysis revealed the particle size distribution of the Zn−Co, Zn−Cu, and Zn−Ni MOFs, with an average size of 442.5 ± 10.96 nm for Zn−Co, 1362 ± 37.72 nm for Zn−Cu, and 1069 ± 29.87 nm for Zn−Ni (Figure 3a and Table S-1 In complex biosamples, metabolites are selectively trapped and identified via LDI. This is envisioned to be facilitated by the bimetallic MOF-NPs that are extremely accessible for guest molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Coal fly ash particles are generally spherical. However, the particles of coal bottom ash are irregular and range from fine gravel to natural sand [8].…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This is due to the high content of SiO2 and Al2O3 in fly ash and bottom ash [6,7]. Two of the aluminosilicate-based materials that can be synthesized from waste ash are geopolymers and zeolites [8][9][10][11][12]. Both have a basic framework composed of alumina and silica compounds.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The p-p stacking interaction present between the benzene ring in MB and the imidazole ring. 58,59 However, the difference in adsorption capacity between ZIF-8 and ZnO did not show the signicant result due to the ZnO has a nearly same mesopore with ZIF-8. Calzada et al, reported that the adsorption capacity of ZnO in MB removal of 7 mg g −1 was lower than ZnO in this report due to the lower mesopore.…”
Section: Photocatalytic Activitymentioning
confidence: 99%